An exploration of health-seeking behaviours among Nigerian Christians in the UK: towards enhanced health services utilisation. Issue 3 (15th March 2016) - Onyigbuo, Chineme Christian; Alexis-Garsee, Camille; van den Akker, Olga
ABSTRACT: Migration from different cultures carries with it some acclimatisation challenges. This study explored various health-seeking behaviours and potential barriers to healthcare utilisation among Nigerian Christians in the UK. This qualitative study involved 10 adult male and female participants, with both interviews and focus group discussion (FG) for data collection (Interviews: n  = 4, FG: n  = 6). Thematic analysis revealed that religious and cultural beliefs were barriers to healthcare utilisation. The implication is that further research on cultural matching between care providers and service users is needed; where religious leaders and health providers from Nigeria can influence health decisions among this migrant community. Limitations of the current study are discussed, with directions for further research identified.